What's PrEP?: Examining Factors Associated with PrEP Peer Navigator Acceptability among Black and Latinx MSM in Western Washington - Pagkas-Bather, Jade (My University, 2019)
Background: HIV PrEP (pre-exposure prophylaxis) is underutilized among Black and Latinx men who have sex with men (MSM). We aimed to estimate interest in peer navigation for PrEP services among minority MSM in Western Washington. Methods: HIV-negative participants aged ≥16 identifying as Black or Latinx MSM completed a REDCap survey in English or Spanish. Survey questions pertained to: demographics, insurance status, access to care, knowledge and attitudes towards PrEP, sexual stigma, mental health, HIV risk assessment, substance and medication use, attitudes towards peer navigation, and importance of peer attributes. Recruitment took place through community-based organizations, flyers, Facebook campaigns, and word of mouth. Factor analysis was used to derive a score for peer navigator interest, and linear regression was utilized to identify associations of participant attributes with this outcome. Results: Among 95 participants (32 Black, 63 Latinx), median age was 30 (IQR 26-40) years. 73% identified as gay, 20% as bisexual, and 5% as queer. Forty-eight percent were interested in peer navigation for PrEP services. In unadjusted regression, being insured (p=0.02), higher sexual stigma score (p=0.006), higher PHQ-9 score (p=0.01), and having a regular medical provider (p=0.002) were associated with higher interest scores; higher income was associated with lower interest (0.001). In adjusted regression, higher income was negatively associated with peer navigator interest (p=0.04). In limited, multivariable analysis, higher stigma score was associated with peer navigator acceptability. Of proposed peer attributes, the most highly rated was matching on sexual orientation (rated “important” or “very important” by 73% of participants), followed by age (50%) and culture (44%). Conclusion: Having insurance and a regular provider may influence men’s interest in peer navigation for PrEP services. Mental health training for peers could increase PrEP access, given greater interest among men with higher sexual stigma and depressive symptoms. Peer interventions for PrEP should match peers to clients on sexual orientation, age, and culture.
Thesis (Master's)--University of Washington, 2019
Keywords: Black; HIV; Latino; Latinx; MSM; PrEP; Epidemiology; Epidemiology